Etika Interaksi Antara Guru dan Siswa dalam Sikap Membantu - Damara Rais, Syazwina Dinda; Suryani, Ira; Rahmadi, Ihsan; Maibang, Supriani; Brutu, Sabilla Meilani; Sabrina, Tasya (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Based on ethics research, the interaction between teachers and students is very necessary because it greatly influences their behavior. In order to become teachers who are expected to fulfill the tasks assigned to us, we must surrender to God Almighty. In addition, the relationship between teacher and student is also one of the factors that influence the success of teaching Islam. Ethics is also a dimension that deserves attention because ethics is the core of educational goals. Ethics are rules, norms, rules or procedures that are often used as guidelines or principles for someone to carry out actions and behaviors that are very important for the lives around us, because they apply to our daily behavior. Ethics guides a person or group in behaving and acting. As educators, teachers must be able to set an example in ethics and communication. To be successful in learning, teachers must provide students with approaches appropriate to their situations, where diversity is important.